A Scenario-based Case Study Approach to Pavement Rehabilitation using Life Cycle Analysis of Recycled Asphalt Materials - Ali, Zahraa K.; Jasim, Abbas F. (Engineering, Technology & Applied Science Research, 2025)
This study evaluates the environmental and mechanical impacts of using Reclaimed Asphalt Pavement (RAP) and Crumb Rubber (CR) in asphalt rehabilitation. A Life Cycle Assessment (LCA) and laboratory testing, complemented by AASHTOWare analysis, were used to assess the mechanical properties and sustainability of various asphalt mixtures. The results show that a composition of 50% RAP and 30% CR offers the best balance of durability, cost efficiency, and environmental benefits. RAP improved rutting resistance, while CR enhanced elasticity and fatigue resistance at lower concentrations. Excessive RAP or CR caused brittleness and susceptibility to cracking. The LCA findings reveal reduced carbon emissions and material consumption, while the cost analysis showed significant savings in construction and maintenance. The AASHTOWare predictions confirmed improved service life and reduced pavement distress under varying traffic and climate conditions. This study demonstrates the potential of RAP and CR for sustainable, cost-effective pavement solutions while maintaining structural performance.